2009
DOI: 10.1089/thy.2008.0221
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Mild Subclinical Hypothyroidism: Prognostic Value of Ultrasound

Abstract: Most patients with SCH and TSH < or = 10 mIU/L do not progress to overt hypothyroidism. The presence of chronic thyroiditis as demonstrated by US increases the evolution of SH to overt hypothyroidism or more severe SCH and thus the need for L-T4 treatment. US findings are important in determining the prognosis of mild SCH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 8 publications
6
75
0
3
Order By: Relevance
“…The causes of SCH resemble the causes of HYPO, where autoimmune thyroiditis is the most frequent cause (9). Table 1 lists studies of the natural history of SCH (10)(11)(12)(13)(14)(15)(16)(17)(18). Progression of SCH to HYPO is in the order of 5-8%/year.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of SCH resemble the causes of HYPO, where autoimmune thyroiditis is the most frequent cause (9). Table 1 lists studies of the natural history of SCH (10)(11)(12)(13)(14)(15)(16)(17)(18). Progression of SCH to HYPO is in the order of 5-8%/year.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in addition to TSH and TPOAb status, lipid profiles and renal function may influence the course of the disease in some ways. A total of 505 mild SCH patients completed the present study, more than several previous studies on this topic [6][7][8][9][10][11]. Compared with other studies, we included individuals aged 40-years or older instead of only elderly people in both sexes [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that baseline characteristics were similar between subjects who accomplished the cohort and these 90 subjects, which meant that our results were representative to some extent. Finally, we did not perform ultrasound tests, which had been reported to have a considerable predictive value in outcomes of SCH, because of the lack of ultrasound scanners and experienced doctors [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations